Iron, magnesium, and titanium isotopic fractionations between garnet, ilmenite, fayalite, biotite, and tourmaline: Results from NRIXS, ab initio, and study of mineral separates from the Moosilauke metapelite. (1st June 2021) - Nie, Nicole X.; Dauphas, Nicolas; Alp, Esen E.; Zeng, Hao; Sio, Corliss K.; Hu, Justin Y.; Chen, Xi; Aarons, Sarah M.; Zhang, Zhe; Tian, Heng-Ci; Wang, Da; Prissel, Kelsey B.; et al.
Abstract: Interpreting isotopic signatures documented in natural rocks requires knowledge of equilibrium isotopic fractionation factors. Here, we determine equilibrium Fe isotope fractionation factors between several common rock-forming minerals using a comparative approach involving three independent methods: ( i ) isotopic analyses of natural minerals from a metapelite from Mt. Moosilauke, New Hampshire, for which equilibration temperature and pressure are well constrained to be near the aluminosilicate triple point (T ≃ 500 °C, P ≃ 4 kbar), ( ii ) Nuclear Resonant Inelastic X-ray Scattering (NRIXS) measurements of Fe force constants of minerals, and ( iii ) Density Functional Theory (DFT) ab initio calculations of Fe force constants of minerals. The minerals studied for Fe isotopes include, in increasing order of their β-factors: garnet < ilmenite ≈ fayalite < biotite < tourmaline < muscovite ≈ plagioclase. Some of this ordering is affected by the presence of Fe 3+ in the minerals, which tends to form stiffer bonds and be associated with heavy Fe isotope enrichments relative to Fe 2+ . We are, however, able to assess the magnitude of the effect of the ratio Fe 3+ /ΣFe on equilibrium fractionation factors, notably on the ilmenite-hematite solid solution. Equilibrium Fe isotopic fractionation factors between garnet, ilmenite, biotite, tourmaline and fayalite are determined. We also report Mg and Ti isotopic compositions of selected Moosilauke minerals that allow us to better constrain the equilibrium fractionation factors for garnet-biotite-tourmaline (Mg isotopes) and biotite-ilmenite (Ti isotopes). We show how the newly determined equilibrium fractionation factors can be used to address diverse problems in Earth and planetary sciences, notably ( i ) Fe and Mg isotopic fractionation during anatexis, ( ii ) Fe isotopic fractionation in lunar ilmenite, and ( iii ) Ti isotopic fractionation during fluvial transport of minerals.